Identifikasi Morfologi, Karakter Agronomi, dan Fenologi Tanaman Gonda (Sphenoclea zeylanica Gaertn) di Kabupaten Tabanan - JUNARTA, I WAYAN; GUNADI, I GUSTI ALIT; PRADNYAWATHI, NI LUH MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Identification of Morphology, Agronomic Characters, and Phenology of Gonda Plant (Sphenoclea zeylanica Gaertn) in Tabanan Regency This study aims to determine the morphology, agronomic characters and phenology of Gonda plant, conducted from November 2014 - February 2015 in Tabanan. Observations conducted to obtain information of Gonda’s cultivars, regional spread, way of cultivation, and environmental conditions. The results showed that there were two cultivars of gonda, i.e. : Gonda Jagoan and Gonda Bali. Based on morphological characters, roots similar to thread, herbaceous trunked, oval – lanceolate leaves, and fascicle flower shaped. Based on agronomiccharacters, crop consumptive was done 18-20 days after transplanting with 26,13 – 58,01 g fresh weight / plant and 3,11 – 6,45 g dry weight / plant. Phenology were beginning with germination at 1-30 days after sowing seeds, flowering was 10-20 days after transplantingand senescenswas 30-50 days after transplanting.
Keywords: Sphenoclea zeylanica; morphology; agronomy; phenology